Legal analysis of exceptions to informed consent in biomedical research in Costa Rica - Alpízar Arce, Megan (2024)
Biomedical research is crucial for medical, technological and social advancement, allowing improvements in disease prevention and treatment. In all research, the well-being of the participants must be prioritized over any possible economic or scientific benefit. The mechanism used to ensure the dignity and autonomy of patients is informed consent. The aim of this work is to analyze the Costa Rican legal framework regarding possible exceptions to informed consent in biomedical research: in observational research, in minors and in people with disabilities. The importance of adapting the regulations to protect the rights of participants is concluded, guaranteeing their participation in ethical and safe research, without compromising scientific advances.